When and why women might suspend PrEP use according to perceived seasons of risk: implications for PrEP-specific risk-reduction counselling. Issue 9 (1st September 2016) - Namey, Emily; Agot, Kawango; Ahmed, Khatija; Odhiambo, Jacob; Skhosana, Joseph; Guest, Greg; Corneli, Amy
Abstract: Oral pre-exposure prophylaxis (PrEP) using the antiretroviral drug emtricitabine/tenofovir disoproxil fumarate (Truvada) has been shown to dramatically reduce the risk of HIV acquisition for women at higher risk of infection if taken daily. Understanding when and why women would intentionally stop using an efficacious oral PrEP drug within the context of their 'normal' daily lives is essential for delivering effective PrEP risk-reduction counselling. As part of a larger study, we conducted 60 qualitative interviews with women at higher risk of HIV in Bondo, Kenya, and Pretoria, South Africa. Participants charted their sexual contacts over the previous six months, indicated whether they would have taken PrEP if available and discussed whether and why they would have suspended PrEP use. Nearly all participants said they would have used PrEP in the previous six months; half indicated they would have suspended PrEP use at some point. Participants' reasons for an extended break from PrEP were related to partnership dynamics (e.g., perceived low risk of a stable partner) and phases of life (e.g., trying to conceive). Life events (e.g., holidays and travel) could prompt shorter breaks in PrEP use. These circumstances may or may not correspond to actual contexts of lower risk, highlighting the importance of tailored PrEP risk-reduction counselling.